A Retrospective and Prospective Study on EGFR Mutations in Lung Carcinomas - Pothina , Yugandhar; Vahini , Gudeli; Shree , M. Lalitha; Asha , Thota (Advanced Concepts in Medicine and Medical Research Vol. 4, 2023)
This chapter aim to study epidermal growth factor receptor expression by immunohistochemistry in diagnosed cases of Non- small cell carcinomas of lung at our institute and to determine the value of EGFR test by immunohistochemistry in predicting response to targeted therapy and clinical outcome. Tumours with amplified EGFR are more likely to have a significant component of solid growth, association between EGFR amplification. Lung cancer is one of the top causes of cancer fatalities in men and women alike. Non-small cell lung carcinomas, which account for the vast majority of lung malignancies (about 75%), have proven challenging to treat due to a poorly known pathological mechanism. Recent advances in cell signaling networks that control cell survival have revealed genetic and regulatory flaws that inhibit cell death, enhance cell division, and drive tumorogenesis. A two-year retrospective and prospective investigation of bronchial samples that were diagnosed as non-small cell carcinoma at our institute, together with the patients' responses to targeted therapy and the expression of the epidermal growth factor receptor immunohistochemical marker. The finding showed that Out of twenty- nine (29) cases of lung malignancies majority were Non -small cell carcinomas- twenty- seven cases (27), of which adenocarcinomas were seventeen (17) cases topped the list, followed by squamous cell carcinomas (5) cases, malignant epithelial lesions (3) cases and poorly differentiated carcinomas (2) cases. There were two (2) cases of small cell carcinomas. Fifteen cases of non-small cell carcinoma had EGFR mutations, and twelve patients were put on Gefitinib and Erlotinib targeted therapy. All twelve of them responded favorably to chemotherapy. The majority of non-small cell carcinomas of the lung, including all adenocarcinomas in non-smokers, have mutations in the epidermal growth factor receptor (EGFR). Patients' clinical outcomes could be anticipated. Targeted chemotherapy produces a noticeable effect.